Evolution of Energy Landscapes: A Regional Case Study in the Western Netherlands - de Jong, Jolanda; Stremke, Sven (Sustainability, 2020)
While the transition to renewable energy becomes a main driver of landscape change, few publications discuss the historical transformation of landscapes for the development of energy—commonly referred to as energy landscape. The research reported in this paper investigates the evolution of energy landscapes in the Western Netherlands—a region shaped by peat extraction and dotted with windmills. Five periods have been identified, dominated by wood, peat, wind, fossil fuels, and modern renewables, respectively. During each period, the landscape coevolved with the new energy source hosting new energy infrastructure. The sequence of landscape transformations over the past 10 centuries in the Western Netherlands is illustrated by means of historical paintings, photographs and a series of five georeferenced maps. Our systematic analysis confirms the long-lasting and manifold interrelations between energy development and landscape transformation at the brink of another energy transition. This paper presents the first all-encompassing application of the analytical framework for the study of energy landscapes proposed earlier. The three main qualifications—substantive, spatial, and temporal—provided a clear framework for the systematic study of landscape transformations at the regional scale.